Sexual transmission of infections across Europe: appraising the present, scoping the future. (10th May 2022) - Geretti, Anna Maria; Mardh, Otilia; de Vries, Henry J C; Winter, Andrew; McSorley, John; Seguy, Nicole; Vuylsteke, Bea; Gokengin, Deniz
Abstract : Objectives: Our journal partnered with the Europe section of the International Union against STI (IUSTI) at a workshop held at the 18th European AIDS Conference in London on 30 October 2021. The workshop reviewed epidemiological trends and discussed STI care provision within HIV services across Europe. Methods and Results: We started by highlighting trends in bacterial STIs reported to the European Centre for Disease Prevention and Control from countries in the European Union/European Economic Area. This showed that notifications of bacterial STIs reached an all-time high in 2019, but are expected to be impacted by the COVID-19 pandemic in 2020–2021. We then reviewed the evolving relationship between STIs and HIV and pointed out how antiretroviral treatment and pre-exposure prophylaxis remain highly effective against HIV transmission despite the rising incidence of STIs. Within emerging concepts in STIs, we appraised the benefits and risks of asymptomatic screening for chlamydia, and also considered the potential perils of routinely testing for agents that lack a defined role in disease. Finally, we discussed standards of STI care for people living with HIV, informed by a brief survey of IUSTI Europe country representatives and members of the Euroguidelines in Central and Eastern Europe network. Conclusions: The survey indicated substantial variability and identified key improvement targets: fighting barriers to effective service provision and access, increasing diagnostic capability and taking leadership in driving up the quality of care. We must not forget the STI-related needs of the many people who will be living with HIV for decades into the future.